2007
DOI: 10.1063/1.2431366
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement effect on Gd2O3 clusters

Abstract: The evolution of the gap of a nanoscaled insulator material, namely, Gd 2 O 3 , has been observed by means of vacuum ultraviolet excitation spectra of a dopant ͑Eu 3+ ͒. The nanoparticles have been synthesized by the low energy cluster beam deposition technique and grown afterward by different annealing steps. A gap shift towards the blue is observed, similar to what is observed in semiconductor nanoparticles. Despite the strong ionic character of the material, the evolution exhibits a behavior similar to cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 27 publications
6
58
1
1
Order By: Relevance
“…In this case a possibility to obtain superfast scintillation response thanks to Wannier exciton-based luminescence response is of interest and high light yield and promising energy resolution was found in [155] as well. In the nanocrystals of insulating wide band-gap solids the phenomena of band-gap widening or change of radiative lifetime of a rare earth emission center in the nanocrystal due to a different dielectric constant of surrounding medium were studied [156,157]. The Eu-doped hexagonal BaCl 2 nanocrystals in the glass matrix have shown surprisingly high scintillation efficiency and can possibly compete with CdWO 4 single crystals in imaging applications [158].…”
Section: Orthosilicate Single Crystalsmentioning
confidence: 99%
“…In this case a possibility to obtain superfast scintillation response thanks to Wannier exciton-based luminescence response is of interest and high light yield and promising energy resolution was found in [155] as well. In the nanocrystals of insulating wide band-gap solids the phenomena of band-gap widening or change of radiative lifetime of a rare earth emission center in the nanocrystal due to a different dielectric constant of surrounding medium were studied [156,157]. The Eu-doped hexagonal BaCl 2 nanocrystals in the glass matrix have shown surprisingly high scintillation efficiency and can possibly compete with CdWO 4 single crystals in imaging applications [158].…”
Section: Orthosilicate Single Crystalsmentioning
confidence: 99%
“…The gap for the AFM structure appears to be larger than that of the FM one, as Ayuela et al 56 and Ning et al 55 found in small clusters, using respectively the PBE functional on Gd 2 O 3 and the B3LYP functional on Gd 12 O 18 . Note that conductivity measurements provide a gap 59,60 Therefore, the use of pure GGA, despite its usual poor description of strongly correlated electrons, is found sufficient to describe with reasonable accuracy the electronic structure of Gd 2 O 3 . In particular, Gd 2 O 3 is found insulating as in experiments.…”
Section: Electronic Structurementioning
confidence: 99%
“…The band gap increase of a crystal due to exciton quantum confinement is a well known phenomenon in direct gap semiconductors like GaAs, GaN or CdSe. To a lesser extent, similar increase is observed also in insulating Gd 2 O 3 :Eu nanocrystals (Mercier et al, 2007). In this material the reduced size can strongly influence the relative population of the dopant energy levels and the width of emission lines (Mercier et al, 2006); moreover, the presence of dopant ions on the nanocrystal surface can be evidenced by appearance of a specific emission band (Mercier et al, 2004).…”
Section: Introductionmentioning
confidence: 79%
“…Nanocrystals of Y 2 O 3 doped with europium or terbium were produced by condensation from gas phase (Bihari et al, 1997;Meltzer et al, 1999), sol-gel (Goldburt et al, 1997) or combustion (Muenchausen et al, 2007) methods. Gd 2 O 3 :Eu was produced by sol-lyophilization (Louis et al, 2003;Mercier et al, 2004Mercier et al, , 2006 and CBD (Cluster Beam Deposition) (Mercier et al, 2007) techniques. The band gap increase of a crystal due to exciton quantum confinement is a well known phenomenon in direct gap semiconductors like GaAs, GaN or CdSe.…”
Section: Introductionmentioning
confidence: 99%